SECONDARY ANALYSIS OF ASSOCIATION OF INTRAOPERATIVE END TIDAL CO2 LEVEL WITH POSTOPERATIVE COMPLICATION: AN OBSERVATIONAL STUDY - Vishal Bhatnagar; Sashikant Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective:This study aimed to investigate the associations between intraoperative end-tidal CO₂ (ETCO₂) levels and postoperative outcomes, including respiratory and cardiovascular complications, ICU stays, and 30-day mortality. Methodology: A secondary analysis of observational study was conducted, involving 10,00 adult patients who underwent various surgical procedures. Patients with intraoperative ETCO₂ levels measured at least three times were included, while those with incomplete data or surgeries lasting less than 60 minutes were excluded. Data on ETCO₂ levels, patient demographics, surgical details, and postoperative outcomes were collected and analyzed using multivariate regression and subgroup analyses to identify significant associations. Results:Elevated ETCO₂ levels (>40 mmHg) were significantly associated with higher rates of respiratory complications (25%), cardiovascular instability (20%), prolonged ICU stays (mean: 6.2 ± 1.8 hours) and increased 30-day mortality (12%). Subgroup analysis revealed that older patients (≥45 years), those with higher ASA classifications (III-IV), and individuals undergoing emergency surgeries experienced worse outcomes compared to their counterparts. Lower ETCO₂ levels (30–35 mmHg) were associated with better postoperative recovery and reduced complication rates. Conclusion:This study highlighted the critical role of intraoperative ETCO₂ monitoring in predicting postoperative outcomes. Elevated ETCO₂ levels were strongly associated with adverse outcomes, emphasizing the need for tailored ventilation strategies and vigilant intraoperative management, particularly in high-risk populations. These findings provided valuable insights for optimizing perioperative care and improving patient safety.